Decentralized Storage in Smart City Data Infrastructure SWOT Analysis - Nuraeni, Rani; Elisa Ananda Natalia; Chua Toh Hua; Nanda Septiani; Ipang Sasono (IAIC Bangun Bangsa, 2026)
The rapid growth of data volume and complexity in modern urban environments has created a critical need for storage systems that are secure, scalable, and resilient. This background emphasizes the urgency of adaptive data infrastructure to support smart city development. This study aims to provide a comprehensive SWOT analysis of decentralized storage in strengthening smart city data infrastructure. A qualitative descriptive-analytical approach is employed, using systematic literature review and document analysis to identify key internal and external strategic factors. The findings reveal key strengths, including enhanced data security, high resilience, and scalability. However, weaknesses such as implementation complexity, latency issues, and dependency on network stability are also noted. Opportunities lie in the integration with Internet of Things (IoT) ecosystems, growing public awareness of data privacy, and emerging collaborative economic models. Meanwhile, threats include regulatory ambiguity, lack of standardization, and evolving cybersecurity risks. This study contributes a strategic framework to assist policymakers, urban planners, and technology stakeholders in integrating decentralized storage systems into smart city architectures. In alignment with the Sustainable Development Goals (SDGs), particularly Goal 11 (Sustainable Cities and Communities) and Goal 9 (Industry, Innovation, and Infrastructure), the research highlights the importance of secure, inclusive, and adaptive digital infrastructure in advancing sustainable urban development.